(untitled) (Revista Brasileira de Contabilidade e Gestão, 2020)
The 1988 Constitution, the so-called “Citizen Constitution”, has radiated effects on the State Constitutions and Municipal Organic Laws with regard to social participation in government decisions and this goes hand in hand with the recognition of a certain collectivity for the importance of this social role, in proportion to the transparency and the accessibility given, by representatives or governments, to these mechanisms. In the City Council of Cachoeira do Sul, there are mechanisms available to citizens who dialogue with this social participation. The work analyzes each of them, aiming to measure them and verify the presence of public governance initiatives. The problem that arises in this context is whether with these forms of social participation the concepts of governance are achieved. The theoretical foundation was based on three pillars: Governance, under the aspect of transparency, Participatory Democracy, through the exercise of citizenship, and Municipal Public Management, under the bias of the role of the minor entity in our federation and how participation operates in political and administrative decisions. The results show each instrument of participation within the space delimited by the study, the years 2017 and 2018, depending on the proposed empiricism, the exercise of parliamentary mandate in the 17th legislature. The final considerations bring the quantitative analysis of these participation mechanisms and from that an analysis is made on the fulfillment of the proposed objectives, as well as the answers to the problem presented in this study are presented.